2023
DOI: 10.11591/ijphs.v12i1.22011
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between family support system with maternal postpartum rage

Abstract: This study investigated the mediating effect of social support with postpartum rage on young mothers during the first to twenty-four months. Method in this research is c a cross-sectional survey design was used in this quantitative non-experimental research. Subject of young mothers who have delivered the children aged one to twenty-four months women who lived in the area of west Sumatera. This study used edinburgh postnatal depression scale (EPDS) to measure which focuses on postpartum rage and the social sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This means that social support does not have a direct effect on postpartum depression, and its effect is only indirect, by increasing resilience. Previous studies have shown that the lack of social support is an important risk factor for postpartum depression and there is a negative correlation between postpartum depression and the level of social support for women (5,(22)(23)(24). Some studies also indicated that low social support from mothers all over the world had a direct relationship with postpartum depression (7,25) which was not consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that social support does not have a direct effect on postpartum depression, and its effect is only indirect, by increasing resilience. Previous studies have shown that the lack of social support is an important risk factor for postpartum depression and there is a negative correlation between postpartum depression and the level of social support for women (5,(22)(23)(24). Some studies also indicated that low social support from mothers all over the world had a direct relationship with postpartum depression (7,25) which was not consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Support resources include emotional-informational support, tangible support, positive social interaction and kindness (4). The results of previous studies showed that women who reported higher levels of social support had less depressive symptoms during the postpartum period compared to women who had less support networks (5)(6)(7).…”
Section: Structural Model Of Postpartum Depression Based On Social Su...mentioning
confidence: 94%
“…Inadequate milk production is one reason mother stop breastfeeding early [3]. This can raise psychological disturbances in breastfeeding mothers, because they feel unable to support the increase baby's weight and meet his needs [4]. A mother's health or sickness, nursing ISSN: 2252-8806 …”
Section: Introductionmentioning
confidence: 99%
“…Through its function as a mediator, satisfaction helps to elucidate the causal pathways and mechanisms underlying various phenomena, making it a valuable tool for researchers seeking to deepen their understanding of human behavior and decision-making processes [13]- [17]. A study by Wexler et al [18] underscores the importance of providing women with access to enhanced emotional support and targeted information resources in the postpartum period, as these interventions can help to mitigate the challenges and stressors commonly experienced during this critical phase of maternal health and promote positive outcomes for both mother and child [19]. Revealed that social support is needed for women.…”
Section: Introductionmentioning
confidence: 99%